2020
DOI: 10.21521/mw.6457
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplements containing silymarin as a supportive factor in the treatment of canine hepatopathies

Abstract: We review canine dietary supplements, in particular silymarin and its hepatoprotective properties. Dietary supplements should be considered complements to conventional drug treatments, helping to prevent health issues, such as nutritional deficiencies and organ dysfunctions. The market for veterinary supplements is growing rapidly. Pet owners are increasingly eager to provide their animals with the best care available. The rapidly growing market of supplements is an opportunity for both the industry and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…The hepatoprotective properties of silymarin, containing silybin, are mainly associated with its antioxidant, anti brotic, anti-in ammatory and cholagogic effect [14]. Moreover, silymarin accelerates liver regeneration [57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hepatoprotective properties of silymarin, containing silybin, are mainly associated with its antioxidant, anti brotic, anti-in ammatory and cholagogic effect [14]. Moreover, silymarin accelerates liver regeneration [57].…”
Section: Discussionmentioning
confidence: 99%
“…On a molecular basis, silymarin inhibits lipid peroxidation and synthesis of reactive oxygen species. It has also been found that silymarin interacts with cell and mitochondrial membranes, modifying the ux of substances through them [14]. In a regular small animal practice, it might be challenging to accurately identify the exact liver disorder (following WSAVA guidelines) due to the lack of medical equipment and nancial limitations, so symptomatic treatment with silybin is fully acceptable and reasonable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hepatoprotective properties of silymarin, containing silybin, are mainly associated with its antioxidant, antifibrotic, anti-inflammatory and cholagogic effect [ 14 ]. Moreover, silymarin accelerates liver regeneration [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Watson [ 13 ], 12% of dogs in United Kingdom were postmortem diagnosed with chronic hepatitis. The etiology may vary from infectious agents such as canine adenovirus 1 (CAV-1) or leptospirosis, to non-infectious factors like neoplasia, poisoning, or inherited malformations [ 14 ]. Regardless of the underlying problem, appropriate feeding should be considered as an effective mean of handling liver diseases.…”
Section: Introductionmentioning
confidence: 99%